La conciliación administrativa y su eficacia para resolver conflictos laborales en la Dirección Regional de Trabajo y Promoción del Empleo de Loreto 2019 - Linares Guimet, Angello Edward (2022)
The content of this report fundamentally addresses establishing the effectiveness of administrative labor conciliation to resolve labor disputes that are presented to the administrative authority of the Regional Directorate of Labor and Employment Promotion of Loreto in 2019. In the theoretical framework The background, concepts, purpose, assumptions of application and other features that characterize Conciliation are presented, and administrative conciliation is special. The type of research is non-experimental, with a quantitative approach, with a descriptive design, with a retrospective and transversal cut. The study population consisted of 94 administrative conciliation files processed before the Subdirectorate of Free Legal Defense and Worker Counseling, with 100% of the total population as a sample. The technique used to collect the information was direct observation and documentary analysis of the conciliation minutes, while the instrument used was the documentary analysis guide. The analysis of results was done through content analysis. The main findings discovered have to do with the importance of Administrative Conciliation as an alternative and effective mechanism for the resolution of disputes of a socio-labor nature.